Statistical Approach To Using Metallurgical Data To Improve The Accuracy And Information Obtained From Financial Analyses - K. A. Altman; D. L. Taylor; Ross W. Smith (Society for Mining, Metallurgy & Exploration, 2003)
Traditional sensitivity analysis of metallurgical data has the potential to overestimate the value of mining projects. Such analyses provide no information about the probability of the results. Simulations that rely on the input of statistical information provide more realistic predictions of the value of future projects and offer additional information regarding the probability of the outcome.